Michel Bras and Alain Boudier, and Christian Millau: Le Livre de Michel Bras - S, E.M. (Petits Propos Culinaires, 1992)
Michel Bras and Alain Boudier, and Christian Millau: Le Livre de Michel Bras: Editions du Rouergue, Rodez, 1991: 315 pp, colour photography by Willy Abplanalp and Alain Willaume: 450 French francs.